2012
DOI: 10.1109/tbc.2012.2191031
|View full text |Cite
|
Sign up to set email alerts
|

Perceived 3D TV Transmission Quality Assessment: Multi-Laboratory Results Using Absolute Category Rating on Quality of Experience Scale

Abstract: International audienceInspired by the rapidly increasing popularity of 3D movies, there is an industrial push for 3DTV services to the home. One important factor for the success and acceptance by the viewers is a positive quality of experience (QoE) of the new service when delivered. The questions of how to efficiently deliver 3DTV service to the home, and how to evaluate the visual quality perceived by end users are a recent research focus. We have investigated users' experience of stereoscopic 3D video quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Traditional approaches to evaluate QoE by means of single stimulus methodologies fail to capture the multi-dimensionality of 3D video. They seem to be mainly evaluating one component, namely pictorial quality, as can be seen in [33,55]. In these studies, it can be observed that 3D QoE is not rated higher than 2D QoE.…”
Section: Model Of 3d Video Qoementioning
confidence: 93%
“…Traditional approaches to evaluate QoE by means of single stimulus methodologies fail to capture the multi-dimensionality of 3D video. They seem to be mainly evaluating one component, namely pictorial quality, as can be seen in [33,55]. In these studies, it can be observed that 3D QoE is not rated higher than 2D QoE.…”
Section: Model Of 3d Video Qoementioning
confidence: 93%
“…Many research efforts are currently being oriented to the development of new technologies devoted to immersive communication, virtual reality and interactive media [20,36]. As a result, providing high audiovisual quality through the combination of emerging audio and video formats is a major objective in audiovisual research and future broadcasting applications [61,63,37].…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that it is possible to include undistorted sequences as test clips to allow a better analysis of the results, which is usually called ACR with hidden references. Moreover, this method has been used in various VQEG [206,207] projects and in many tests with 3D video, as in [212].…”
Section: Subjective Evaluation Methodologiesmentioning
confidence: 99%
“…Moreover, this effect mainly affects zones of the images containing moving elements, and it could propagate to several frames (until a new I-frame is correctly received), due to the use of reference frames in the encoding process. Although these effects already cause severe degradations of the QoE in 2D video, their impact in 3D content may be even more annoying, since they could cause binocular rivalry when the same region in both stereo views is affected differently [57,212]. This effect is deeply investigated in the following section 5.3.…”
Section: Main Perceptual Effectsmentioning
confidence: 98%
See 1 more Smart Citation